Antiklerikalismus und Exklusionsrhetorik in der Tang-Zeit: Religionspolitik im Denken Li Deyus - Höckelmann, Michael (Bochumer Jahrbuch zur Ostasienforschung, 2010)
During the Tang Dynasty, officials, who are often described as “Confucians,” were involv- ed in policies that aimed at controlling the religious congregations of Buddhism and Daoism. At the same time, pseudo-religious free-riders, the so called fangshi (“esoteric experts”), regularly appeared at the court and lured the emperor away from government business by pretending to support his search for immortality with their methods. They thereby constituted a threat to the claim of the officials to a monopoly on sharing the imperial power. Furthermore, officials saw themselves as transmitters of a “civil religion” or “theology” of correct govern- ance, which was not limited to the Confucian canon, but embraced other figures such as Laozi and the Yellow Emperor as well. My essay takes Li Deyu (787–850) as an example, who was one of the most prominent officials of the Tang Dynasty and served as chancellor during the severest religious persecution in Chinese history. I show how he drew arguments from historiographic and philosophical sources, in order to bolster his position against Daoists orfangshi and protect the civil religion. I will further show how he flexibly used rhetorical strategies to support the persecution of Buddhism on the one hand, and to justify the com- patibility of Buddhism with Confucian and Daoist ethics on the other.